Consecuencias del Conflicto Armado Interno Colombiano en la Identidad Cultural y Percepción del Self de los Habitantes del corregimiento Betania de la Localidad del Sumapaz (2022)
The Colombian internal armed conflict has marked the history of Colombia and its inhabitants, leaving a shadow of violence, death, sadness and disappointment in its wake, it is considered necessary to approach from psychology, problems of the context that allow studying how they originated. , how they evolved and what were the consequences that they leave in the affected communities victims of the Colombian internal armed conflict, for this in the present degree work, it is intended to investigate the consequences of this in the cultural identity and the self, in the inhabitants of the Corregimiento Betania, in the town of Sumap az, in the city of Bogotá. For this, qualitative research is approached, with an exploratory and phenomenological methodology that uses discourse analysis to evaluate the information collected from psychoanalysis.